CHRONIC ANTICONVULSANT EFFECT OF GHEE PREPARED WITH HUMBOLDTIA VAHLIANA (ATTUVANCHI BARK) – AN ETHNOMEDICINAL PRACTICE IN KERALA (International Journal of Ayurveda and Pharma Research, 2020)
Humboldtia vahliana Wight, Ic.tt belongs to the family Caesalpiniaceae is an unarmed erect small tree, commonly called as Attuvanchi in Malayalam. Stem bark which is used in the treatment of apasmara by tribal healers of Urulanthanni area, Ernakulum district in Kerala, India. Apasmara of Ayurveda aptly comes under the epilepsy of modern literature, especially under tonic-clonic / generalized seizure. Epilepsy (Apasmara) is an electrical disturbance resulting from sudden, recurrent, and disorderly discharge of neurotransmitter in brain cells. The prevalence of epilepsy has been estimated at 5-10 persons per1000. In this study ghee prepared with Humboldtia vahliana (GHV) was tested for chronic anticonvulsant effect by Maximal electro shock seizure test in female wistar albino rats (150-200mg). The experiment was carried out with 5 groups having 6 albino rats per group. ‘Phenytoin’ was given to the standard group. Group I, III, IV, V were given distilled water, vehicle (cow’s ghee), effective dose of GHV, double dose of GHV respectively. Complete abolition or reduction time (in seconds) of hind limb extension is considered as anticonvulsant activity of drug. At the end of experiment effective dose of GHV and double dose of GHV showed significant chronic anticonvulsant action as compared with vehicle and control. Group IV (effective dose) was able to reduce the Time of Tonic Hind Limb extension (THE) by 44.34%with p value 0.007 (compare with control). Group V (double dose) was able to reduce the Time of Tonic Hind Limb extension by 59.53% with p value 0.004 (compared with control). This change was statistically significant at p